Analysis of Construction Costs on the Improvement of the Dupak Road Section in Surabaya City - Adiputra, Reza; Wulandari, Esti; Witjaksana, Budi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The rapid growth of traffic in urban areas, especially on the Jalan Raya Dupak Surabaya section, has a significant impact on the decreasing age of road pavement plans and increasing the need for construction costs. This study aims to analyze and calculate the estimated cost of improving the Dupak road section in Surabaya City. Methods Analysis of average daily traffic data (LHR), calculation of single axle equivalent load (ESAL), and rigid pavement structure design taking into account the underlying soil conditions and projected traffic load over the life of the plan of 40 years. The results of the study show that traffic growth of 5.6% per year leads to a significant decrease in the life of the plan if it is not anticipated with the right pavement design. The estimated cost of road improvement reaches Rp 11,513,568,000.00. It is hoped that this research will help in planning the improvement of urban arterial roads to maintain the sustainability and efficiency of transportation infrastructure